G91-deletion in βA3/A1-crystallin induces cellular and molecular changes in mouse lenses leading to congenital cataract development - Akosua K. Boateng; Roy Joseph; Om P. Srivastava (PLoS ONE, 2025)
CRYβA1-ΔG91 (βA3ΔG91) is a mutational hotspot in CRYβA1, which causes autosomal dominant congenital nuclear cataract in humans and mice. Previous in-vitro studies of recombinant βA3ΔG91 showed defective folding, decreased solubility, and aberrant oligomerization of βA3ΔG91 with other crystallins. Emerging evidence demonstrates an association between autophagy and βA3ΔG91-induced congenital cataracts. To gain further understanding of the molecular mechanism of congenital cataract development in βA3ΔG91 mice, we examined the βA3ΔG91- vs WT- lenses for complete gene profiling, lens epithelial cell (LEC) proliferation and migration, and lens epithelial-fiber cell differentiation. We also determined the changes in crystallin proteomic profiles in water-soluble, water-insoluble-urea-soluble, and water-insoluble-urea-insoluble fractions. Our results show that relative to WT lenses, the βA3ΔG91 lenses showed: (A) downregulation of genes associated with LECs proliferation and migration (B) abnormal suture line pattern, (C) significant reduction in proliferation and migration of LECs, (D) abnormal F-actin distribution, (E) increased high molecular weight (HMW) peak, and (F) insolubilization and degradation of crystallins and other lens proteins. Together, these defects contribute to the formation of the lens opacity in βA3ΔG91 mice lenses.